AB0738 SAPHO OR PSORIATIC ARTHRITIS?: EVALUATION OF CASPAR CRITERIA IN A COHORT WITH SAPHO. (2nd June 2020) - Aparicio Rovira, M.; Aparicio Espinar, M.; Gifre, L.; Holgado, S.; Martínez-Morillo, M.; Riveros, A.; Sanguesa, C.; Prior-Español, Á.; Nack, A.; Casafont-Solé, I.; Olive, A.; Mateo, L.
Abstract : Background: SAPHO syndrome (synovitis, acne, pustulosis, hyperostosis and osteitis) is an acronym created with the aim of encompassing within the same entity the findings present in a heterogeneous group of patients with various osteoarticular and cutaneous disorders. For years it has been debated whether it is an entity itself or if, on the contrary, it is a specific phenotype of psoriatic arthritis. Objectives: Determine the relationship between SAPHO syndrome and psoriatic arthritis by comparing the classic criteria of SAPHO with CASPAR in patients previously diagnosed with SAPHO. Methods: A retrospective study where patients with a diagnosis of SAPHO in the same center (1984-2018) were reviewed. Of a total of 95 patients that met the criteria of Benhamou et al., 46 were excluded due to lack of information to complete the minimum necessary data, so 39 patients were finally included in the study. Demographic data were registered, age at diagnosis, CASPAR criteria (active psoriasis, history of own or familial psoriasis, nail psoriasis, negative RF, dactylitis and new formation/juxta-articular bone proliferation), classical criteria of SAPHO and HLAB27. For the statistical analysis, a Chi-square is applied to determine the differences between the groups with / without CASPAR criteria. Results: Of the sample of 39 subjects diagnosed with SAPHO, 15 patients (38%) met CASPAR criteria (4M/11W), with a median age at diagnosis of 42 years (range 21-50). Of them, 8 (60%) had active cutaneous psoriasis, 10 (73%) had a family or personal history of psoriasis, 6 (40%) had psoriatic nail dystrophy, 14 (93%) had negative FR, 3 (20%) had presented some episode of dactylitis and 10 (73%) had juxta-articular new bone formation. Of the 15 patients who met CASPAR criteria, 9 (67%) had synovitis, 2 (13%) acne, 4 (26%) pustulosis, 13 (87%) hyperostosis and 12 (80%) osteitis. HLAB27 was positive in 1 patient (2.5%) of the group that met CASPAR criteria. Of the patients who did not fulfill CASPAR criteria (9M/15W), the median age at diagnosis was 44.5 years (range 10-70). None of them had active cutaneous psoriasis, psoriatic nail distrophy or dactylitis, 1 (4%) had a family or personal history of psoriasis, all had RF- and 3 (12.5%) had juxta-articular bone new formation (Table 1). Synovitis was observed more frequently in patients who met CASPAR criteria than in those who did not (67% vs 25%, p 0.01). In contrast, osteitis was present more frequently in patients who did not meet CASPAR criteria (80% vs 96% p 0.05) and pustulosis, although it was not statistically significant (50% vs 26%, p 0.07). Among patients who did not meet CASPAR criteria only 1 met the 5 classic SAPHO criteria and another 3 met 4. Conclusion: Approximately one third (38%) of patients diagnosed with SAPHO meet criteria for psoriatic arthritis, the most notable variables being active psoriasis or a history of psoriasis. Synovitis manifests more frequently in patients with CASPAR criteria and osteitis more present in patients who did not meet them. Acknowledgments: Rheumatology Service of the Germans Trias i Pujol Hospital Disclosure of Interests: None declared